Mechanisms involved in the cardioprotective effect of avocado consumption: a systematic review - Caldas, Ana Paula Silva; Chaves, Larissa Oliveira; Silva, Letícia Linhares Da; Morais, Dayane De Castro; Alfenas, Rita de Cássia Gonçalves (International Journal of Food Properties, 2017)
The objective of this review was to verify the effects of avocado consumption on cardiovascular diseases (CVDs) risk factors. A systematic search was conducted in electronic databases using the descriptor avocado, combined with CVD, monosaturated fat, antioxidant, lipoprotein, and inflammation, and their respective terms in Spanish. The review was carried out in pairs, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) recommendations. Initially, 234 studies were identified. After selection, eight articles were included. All the studies were randomized, most were crossover studies, and involving adult subjects. Total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-c), triglycerides (TG), platelet aggregation, and apolipoproteins reductions; besides high- density lipoprotein-cholesterol (HDL-c) and serum lipid peroxidation increases; Ikappa-B protein (IkB-α) protein preservation; and NF-kappa B (NFκB) inactivation were observed. Thus, avocado consumption exerts a beneficial effect on CVDs prevention, which can be attributed to its mono- unsaturated fatty acids (MUFA) content, especially oleic fatty acid. However, there is no consensus on the amount of avocado needed to confer such benefits.
Keywords: Cardiovascular disease; Dyslipidemia; Oxidative stress; Persea americana; Inflammation